Determination of Ursolic Acid in Extracts From Ligustri lucidum Fruit Using an Electrochemical Method - Feng, Yingpu; Wei, Zheng; Zhang, Junping (Frontiers in Chemistry, 2020)
In this work, we reported a facile wet chemical method for depositing Pt nanoparticles on the surface of boron nitride nanosheets (BNNS-Pt NPs). The deposited nanocomposite was applied for glassy carbon electrode surface modification. The modified electrode was then used for detecting ursolic acid (UA). The results indicate that the BNNS-Pt NPs exhibited excellent electrocatalytic activity towards UA oxidation compared with that of the bare glassy carbon electrode (GCE) and Pt NPs/GCE. The UA oxidation currents is linearly related its concentration from 1 to 1200 pM. The limit of detection can be calculated to be 0.5 pM. In addition, the UA sensor was also successfully used for the determination of UA in Ligustri lucidum fruit samples.